Interferon regulatory factor 1 eliminates mycobacteria by suppressing p70 S6 kinase via mechanistic target of rapamycin signaling. Issue 3 (September 2019) - Zhou, Xinying; Yang, Jiahui; Zhang, Zelin; Zhang, Lijie; Lie, Linmiao; Zhu, Bo; Xu, Lei; Gao, Yuchi; Du, Xialin; Huang, Yingqi; Wang, Ruining; Liu, Honglin; et al.
Highlights: IRF1 is induced in pulmonary TB patients in vivo and in human Mϕs in vitro . IRF1 protects human Mϕs from Mtb infection. IRF1 promotes the expression of several pro-inflammatory cytokines. IRF1 suppresses the mTOR/ p70 S6K cascade to exert its anti-Mtb effect. Summary: Objectives: Although it has been reported that Interferon regulatory factor 1 (IRF1) inhibits Mycobacterium tuberculosis (Mtb) infection via inducible nitric oxide synthase (iNOS) in mice, how it counteracts with mycobacterial infection in human remains largely obscure. This study was conducted to investigated the effect of IRF1 on Mtb infection in human macrophages (Mϕs). Methods: We thus investigated the IRF1 expression by using PBMC and monocytes of pulmonary tuberculosis (TB) patients and human monocyte-derived macrophages (hMDMs) and THP-1-derived macrophages (THP-1-Mϕ). We used gain-of-function and loss-of-function approaches to explore the role of IRF1 on Mtb infection. Results: IRF1 was significantly induced in PBMC and monocytes of pulmonary TB patients in vivo and in human Mϕs in vitro . We demonstrated that IRF1 protects Mϕs from Mtb infection. Concurrently, IRF1 promotes the expression of several pro-inflammatory cytokines including IL-6, TNF-α and IL-8, indicating IRF1-mediated activation of innate immunity upon Mtb infection. Gain-of-function and loss-of-function approaches have demonstrated that IRF1 suppresses the mechanistic target of rapamycin (mTOR)/p70 S6 kinase (p70 S6K) cascade to exert its anti-Mtb effect. Conclusions: The discovery of a novel function of IRF1 in facilitating anti-mycobacterial effect through suppressing mTOR/p70 S6K signaling in Mϕs may provide a promoting therapeutic target for tuberculosis.